Reemergence of Oropouche Virus in the Americas and Risk for Spread in the United States and Its Territories, 2024 - Guagliardo, Sarah Anne J.; Connelly, C. Roxanne; Lyons, Shelby; Martin, Stacey W.; Sutter, Rebekah; Hughes, Holly R.; Brault, Aaron C.; Lambert, Amy J.; Gould, Carolyn V.; Staples, J. Erin (Emerging infectious diseases, 2024)
Oropouche virus has recently caused outbreaks in South America and the Caribbean, expanding into areas to which the virus was previously not endemic. This geographic range expansion, in conjunction with the identification of vertical transmission and reports of deaths, has raised concerns about the broader threat this virus represents to the Americas. We review information on Oropouche virus, factors influencing its spread, transmission risk in the United States, and current status of public health response tools. On the basis of available data, the risk for sustained local transmission in the continental United States is considered low because of differences in vector ecology and in human-vector interactions when compared with Oropouche virus-endemic areas. However, more information is needed about the drivers for the current outbreak to clarify the risk for further expansion of this virus. Timely detection and control of this emerging pathogen should be prioritized to mitigate disease burden and stop its spread.